PERANAN PSIKOLOGI PENDIDIKAN ISLAM UNTUK PENCEGAHAN BULLYING SISWA KELAS VI MI MANBAUL HIKAM BREBES - Siti Nurkhaibah; Arshan Shanie (ARIMA : Jurnal Sosial Dan Humaniora, 2025)
Bullying is a term that refers to acts of violence or oppression carried out by individuals who have more power, whether in terms of age, physical strength, or authority. Bullying behavior can take various forms, such as physical, verbal, and mental/psychological bullying, which can have negative effects on victims, such as bruises, injuries, pain, anxiety, and more. In the long term, the impacts can include psychological disorders and serious social adjustment problems. Educational psychology plays a very important role in efforts to prevent and address bullying cases in schools. Therefore, efficient and comprehensive services are needed for all students, utilizing various techniques and media that can support the role of educational psychology in addressing bullying